2014
DOI: 10.1093/jat/bku011
|View full text |Cite
|
Sign up to set email alerts
|

A Fatality Involving AH-7921

Abstract: A case is presented of a 19-year-old white male who was found dead in bed by a friend. While no anatomic cause of death was observed at autopsy, toxicological analysis of his blood identified AH-7921, a synthetic opioid. AH-7921 was isolated by liquid-liquid extraction into n-butyl chloride from alkalinized samples. Extracts were analyzed and quantified by gas chromatography mass spectrometry in selected ion monitoring mode. The heart blood had an AH-7921 concentration of 3.9 mg/L and the peripheral blood conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 11 publications
3
35
0
1
Order By: Relevance
“…In 2013, AH-7921 was discovered as an active ingredient in synthetic cannabis products in Japan (Uchiyama et al, 2013). It has since been identified in numerous overdose cases across Europe and the US (Vorce et al, 2014;Karinen et al, 2014;Coppola and Mondola, 2014;Katselou et al, 2015;Fels et al, 2017).…”
Section: Novel Synthetic Opioidsmentioning
confidence: 99%
“…In 2013, AH-7921 was discovered as an active ingredient in synthetic cannabis products in Japan (Uchiyama et al, 2013). It has since been identified in numerous overdose cases across Europe and the US (Vorce et al, 2014;Karinen et al, 2014;Coppola and Mondola, 2014;Katselou et al, 2015;Fels et al, 2017).…”
Section: Novel Synthetic Opioidsmentioning
confidence: 99%
“…It is suggested that the primary route of AH-7921 administration is oral consumption; the drug is also taken nasally, sublingually, rectally, and by intravenous injection. Selfreported effects include relaxation, euphoria, analgesia, alertness, nausea, myosis, Kronstrand et al, 2014;Vorce et al, 2014). In one case, the fatal intoxication with a combination of AH-7921 and two synthetic cathinones (Nethylbuphedrone and 3-methylmethcathinone) led to a sudden cardiac arrest (Skowronek et al, 2014).…”
Section: Ah-7921mentioning
confidence: 99%
“…Before 2012, there were few synthetic opioids, primarily fentanyl derivatives; however, AH-7921, 3,4-dichloro-N-[(1-dimethylamino)cyclohexylmethyl]benzamide, emerged in Europe in July 2012 [2,3] and Japan in 2013 [4] . In only 10 months, AH-7921 was involved in severe intoxications and fatalities in four countries [58] and was considered at least a contributing cause of death factor in all cases [7] .…”
Section: Introductionmentioning
confidence: 99%
“…AH-7921, N-desmethyl-AH-7921, di-desmethyl- AH-7921 and one oxidated metabolite were described in two postmortem cases [17] , and the parent compound was stable in blood and plasma for 28 days at room temperature. Vorce et al mentioned two unidentified peaks whose GC-MS fragmentation pattern would match with the desmethyl and di-desmethyl AH-7921 metabolite [8] . Finally, Kronstrand et al detected six metabolites in blood samples from fatal cases including desmethyl AH-7921 and di-desmethyl AH-7921, for which the authors obtained high-resolution product ion spectra, and four hydroxylated metabolites [5] .…”
Section: Introductionmentioning
confidence: 99%